Employing Web Search Query Click Logs for Multi-Domain Spoken Language Understanding - Hakkani-Tür, Dilek; Tur, Gokhan; Heck, Larry; Celikyilmaz, Asli; Fidler, Ashley; Harris, Dustin; Iyer, Rukmini; Parthasarthy, Sarangarajan (IEEE Automatic Speech Recognition and Understanding Workshop, 2011)
In this paper, we describe methods to exploit search queries mined from search engine query logs to improve domain detection in spoken language understanding. We propose extending the label propagation algorithm, a graph-based semi-supervised learning approach, to incorporate noisy domain information estimated from search engine links the users click following their queries. The main contributions of our work are the use of search query logs for domain classification, integration of noisy supervision into the semi- supervised label propagation algorithm, and sampling of high-quality query click data by mining query logs and using classification confidence scores. We show that most semi-supervised learning methods we experimented with improve the performance of the supervised training, and the biggest improvement is achieved by label propagation that uses noisy supervision. We reduce the to error rate of domain detection by 20% relative, from 6.2% to 5.0%.